2019
DOI: 10.7150/ijms.32962
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preconditioning Attenuates Neurological Injury by Preserving Old and Newly Formed HSP72-Containing Neurons in Focal Brain Ischemia Rats

Abstract: Background: Exercise preconditioning (EP + ) is a useful and important procedure for the prevention of stroke. We aimed to ascertain whether EP + protects against ischemic brain injury by preserving heat shock protein (HSP) 72-containing neurons in ischemic brain tissues. Methods: Adult male Sprague-Dawley rats (n=240) were used to assess the contribution of HSP72-containing neurons to the neuroprotective effects of EP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…These mechanisms may involve but not limited to: (1) reducing the poststroke inflammation by reducing the expression and activity of inflammatory cytokines like TNFα, TLRs, and NF-κB after stroke; [44][45][46][47][48][49][50][51][52][53] (2) increasing angiogenesis and neovascularization through increasing the expression of VEGF and VEGF receptors, caveolin, and angiopoietin in the brain; [56][57][58] (3) increasing the BBB integrity and reducing disruption through reducing the post-stroke expression of MMPs and increasing the expression of integrins proteins; [46][47][48]54,55 (4) increasing post-stroke CBF by increasing eNOS activation and NO production; [62][63][64] and (5) increasing neurogenesis and reducing neuronal apoptosis through activation of HIF-1α, HSPs, BDNF, and inhibition of glutamate and caspase activities. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] It is obvious that the preconditioning exercise-induced protection is due to multiple intermeshing mechanisms and pathways. The interplay between these different mechanisms and molecules in the signaling pathways can be the main cause of the ultimate neurovas...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These mechanisms may involve but not limited to: (1) reducing the poststroke inflammation by reducing the expression and activity of inflammatory cytokines like TNFα, TLRs, and NF-κB after stroke; [44][45][46][47][48][49][50][51][52][53] (2) increasing angiogenesis and neovascularization through increasing the expression of VEGF and VEGF receptors, caveolin, and angiopoietin in the brain; [56][57][58] (3) increasing the BBB integrity and reducing disruption through reducing the post-stroke expression of MMPs and increasing the expression of integrins proteins; [46][47][48]54,55 (4) increasing post-stroke CBF by increasing eNOS activation and NO production; [62][63][64] and (5) increasing neurogenesis and reducing neuronal apoptosis through activation of HIF-1α, HSPs, BDNF, and inhibition of glutamate and caspase activities. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] It is obvious that the preconditioning exercise-induced protection is due to multiple intermeshing mechanisms and pathways. The interplay between these different mechanisms and molecules in the signaling pathways can be the main cause of the ultimate neurovas...…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these actions will inhibit cerebral inflammation, cell death, and BBB disruption. [46][47][48][84][85][86] Inhibition of glutamate-induced excitotoxicity by exercise, may lead to reduction in neuronal apoptosis and cell death. [68][69][70][71][72][73][74][75][76] This may be due to reduced calcium ion intracellular influx, increased Bcl2, and reduced Bax leading to reduction in caspases activity, mainly caspase 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have discovered that exercise can exert a neuroprotective effect on cerebral ischemia by regulating HSP-70 (HSP-72). Wang Y. L. et al (2019) demonstrated that the percentage of HSP-72-containing neurons are tightly associated with a degree of ischemic stroke-induced brain injury, and exercise preconditioning can help improve neurological function post-stroke by preserving both the old and newly formed HSP-72-containing neurons. Liebelt et al (2010) found that the expression of Bax and apoptosis-inducing factor (AIF) were reduced, while levels of Bcl-x(L) were increased in response to stroke after exercise.…”
Section: Exercise and Restoration Of Neurovascular Unitmentioning
confidence: 99%